The reliability of back-extrapolation in estimating V˙O2peak in different swimming performances at the severe-intensity domain - Massini, Danilo Alexandre; Simionato, Astor Reis; Almeida, Tiago André Freire; Macedo, Anderson Geremias; Espada, Mário Cunha; Reis, Joana Filipa; Besone Alves, Francisco; Pessôa Filho, Dalton Müller (Frontiers in Physiology, 2022)
The present study aimed to analyze the reliability of peak oxygen uptake (V̇O2peak) estimated by back-extrapolation (BE-V̇O2peak) in different swimming performances in the severe intensity domain.Twenty swimmers (16.7 ± 2.4 years, 173.5 ± 10.2 cm, and 66.4 ± 10.6 kg) performed an incremental intermittent step protocol (IIST: 6 × 250 plus 1 × 200 m, IIST_v200m) to the assessment of V̇O2peak. The V̇O2 off-kinetics used a bi-exponential model to discriminate primary amplitude, time-delay, and time constant (A1off, TD1off, and off) for the assessment of fast-O2debt post IIST_v200m, 200 m single-trial (v200m), and rest-to-work transition at 90% delta (v90%Δ) tests. The linear regression estimated BE-V̇O2peak and the rate of V̇O2 recovery (BE-Slope) post each swimming performance. The ANOVA (Sidak as post-hoc) compared V̇O2peak to the estimates of BE-V̇O2peak at v200m, IIST_v200m, and v90%Δ, and the coefficient of dispersion (R2) analyzed the association between tests.The values of V̇O2peak during IIST did not differ from BE-V̇O2peak at v200m, IIST_v200m, and v90%Δ (55.7 ± 7.1 vs. 53.7 ± 8.2 vs. 56.3 ± 8.2 vs. 54.1 ± 9.1 ml·kg-1·min-1, p > 0.05, respectively). However, the V̇O2peak variance is moderately explained by BE-V̇O2peak only at IIST_v200m and v90%Δ (R2Adj = 0.44 and R2Adj = 0.43, p < 0.01). The TD1off and off responses post IIST_v200m were considerably lower than those at both v200m (6.1 ± 3.8 and 33.0 ± 9.5 s vs. 10.9 ± 3.5 and 47.7 ± 7.9 s; p < 0.05), and v90%Δ (vs. 10.1 ± 3.8 and 44.3 ± 6.3 s, p < 0.05). The BE-Slope post IIST_v200m was faster than at v200m and v90%Δ (-47.9 ± 14.6 vs. -33.0 ± 10.4 vs. -33.6 ± 13.8 ml·kg-1, p < 0.01), and the total anaerobic (AnaerTotal) demand was lower in IIST_v200m (37.4 ± 9.4 ml·kg-1) than in v200m and v90%Δ (51.4 ± 9.4 and 46.2 ± 7.7 ml·kg-1, p < 0.01). The initial phase of the V̇O2 recovery profile provided different (although reliable) conditions to the estimate of V̇O2peak with BE procedures, which was accounted for the effect of anaerobic release on V̇O2 off-kinetics, but compromised, exceptionally, the V̇O2peak estimate in 200 m single-trial.